PENGARUH PENERAPAN MODEL PEMBELAJARAN STUDENT FACILITATOR AND EXPLAINING (SFAE) TERHADAP KEMAMPUAN KOMUNIKASI MATEMATIK SISWA KELAS VII SEMESTER GENAP SMP NEGERI 10 BANDAR LAMPUNG TAHUN PELAJARAN 2016/2017 - Maryani, Ayu (Epsilon: Jurnal Pendidikan Matematika, 2019)
The problems studied in this study relate to the low level of mathematics communication skills of students. The purpose of this study was to determine the effect of applying the Student Facilitator and Explaining (SFaE) learning model on the mathematical communication skills of seventh graders in the even semester of SMPN 10 Bandar Lampung in 2016/2017 Academic Year. This research is using experimental method. The population in this study were all students of class VII of SMPN 10 Bandar Lampung. For the sample taken two classes, namely the first class as the experimental class and the second class as the control class. The data analysis technique uses the t-test which first tested its normality and homogeneity. The instrument in this study used an essay test. From the results of hypothesis testing using the statistical t-hit formula obtained thit = 4.23 from the distribution table at the level of 5% it is known that tdaf = 2.00 proved thit> tdaf so it can be concluded that there is the effect of applying Student Facilitator and Explaining (SFaE) learning models on Mathematical communication skills of seventh grade students in the even semester of SMPN 10 Bandar Lampung Academic Year 2016/2017.